PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR FIQH SISWA MI RINGINSARI SANANKULON BLITAR - M. Ali Muhson; Ahmad Arif Musyafa’ (POJOK GURU: Jurnal Keguruan dan Ilmu Pendidikan, 2023)
Once the researchers conducted research using the method cooperative jigsaw cann finally be concluded that by using cooperative learning jigsaw type can improve students' learning achievement fiqh. The application learn include: The initial phase 1) The teacher divides the 20 grade II in 4 groups of cooperative learning (group home), each group consisted of 5 students, 2) Teacher explains the material in outline only, 3) The teacher divides material into 4 topic. Core Phase 1) Teacher memabagi expert group by counting 1-4, 2) Presentation of the original group, 3) Giving a quiz question. The final stage 1) Provision of post test (test item evaluation). As for increasing student achievement can be seen from the learning process and the value of the final test. In this study, the students showed a positive response to the Jigsaw cooperative learning. It can be known from the results of interviews with representatives of grade II which shows that Jigsaw cooperative learning can enhance students' enthusiasm for learning fiqh lessons